Equilibrium contracts and boundedly rational expectations - Heiner Schumacher; Heidi Christina Thysen (Theoretical Economics, 2022)
We study a principal-agent framework in which the agent forms beliefs about the principal's project based on a misspecified subjective model. She fits this model to the objective probability distribution to predict output under alternative actions. Misspecifications in the subjective model may lead to biased beliefs. However, under mild restrictions, the agent has correct beliefs on the equilibrium path so that the optimal contract is nonexploitative. This allows for a behavioral version of the informativeness principle: The optimal contract conditions on an additional variable only if it is informative about the action according to the agent's subjective model. We further characterize when misspecifications affect the optimal contract. One implication of this characterization is that the scope for belief biases depends on the agent's job, for example, her position in the hierarchy.
Keywords: D03; D82; D86; 330; Bayesian networks; principal-agent relationship; bounded rationality